2023
DOI: 10.1111/eva.13589
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis provides diagnostic tools for the identification of Anastrepha fraterculus (Diptera: Tephritidae) species complex

Carlos Congrains,
Julian R. Dupuis,
Erick J. Rodriguez
et al.

Abstract: Insect pests cause tremendous impact to agriculture worldwide. Species identification is crucial for implementing appropriate measures of pest control but can be challenging in closely related species. True fruit flies of the genus Anastrepha Schiner (Diptera: Tephritidae) include some of the most serious agricultural pests in the Americas, with the Anastrepha fraterculus (Wiedemann) complex being one of the most important due to its extreme polyphagy and wide distribution across most of the New World tropics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 134 publications
1
7
0
Order By: Relevance
“…, 2012; Hernández-Ortiz et al, 2015). Although we did not investigate different morphotypes in this study that would enable us to compare these taxa to the ones described elsewhere (Hernández-Ortiz et al, 2015; Prezotto et al, 2019), the topology we found is remarkably similar to what has been described using transcriptomic and genomic data(Congrains et al, 2021;Congrains et al, 2023), which identi ed three distinct branches for A. fraterculus while supporting a single A. obliqua branch. These diverse A. fraterculus lineages may be subject to distinct selective pressures(Smith-Caldas et al, 2001;Manni et al, 2015), despite their recent divergence.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…, 2012; Hernández-Ortiz et al, 2015). Although we did not investigate different morphotypes in this study that would enable us to compare these taxa to the ones described elsewhere (Hernández-Ortiz et al, 2015; Prezotto et al, 2019), the topology we found is remarkably similar to what has been described using transcriptomic and genomic data(Congrains et al, 2021;Congrains et al, 2023), which identi ed three distinct branches for A. fraterculus while supporting a single A. obliqua branch. These diverse A. fraterculus lineages may be subject to distinct selective pressures(Smith-Caldas et al, 2001;Manni et al, 2015), despite their recent divergence.…”
supporting
confidence: 76%
“…While there is evidence of pre-and postzygotic isolation among some sympatric and allopatric populations of Anastrepha species (Selivon et al, 2005;Vera et al, 2006;Rull et al, 2018), hybridization between A. fraterculus and A. obliqua has successfully produced viable offspring in the laboratory, though following Haldane's rule (Santos et al, 2001). This nding has been corroborated by population studies that indicate gene ow between these species, despite the presence of reproductive barriers (Díaz et al, 2018;Scully et al, 2018;Congrains et al, 2021;Congrains et al, 2023). In this scenario, it is possible that different parts of the genome may introgress differently, so genes with speci c reproductive biases may play a crucial role in differentiation and speciation, making their study of particular relevance for understanding the underlying forces separating Anastrepha species.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations